Variations in water content of soil in apricot orchards in the western hilly regions of the Chinese Loess Plateau - Shi, D. (2020)
Large changes in land use and land cover types have been occurring in the hill and gully regions of the Loess Plateau since the end of the 1990s. This study revealed dynamic variations of soil water in different layers of representative land use and land cover types under different annual precipitation regimes and assessed the effects on soil water circulation in large areas of apricot [Armeniaca sibirica (L.) Lam.] trees, which have extensive and deep root systems. The results show distinct soil water deficit with a water content of generally <17% (60% of field capacity) in the deep layers of the soil profile of the apricot orchards. Several years after afforestation, perennial soil water deficit layers have subsequently developed around the root zone or even extended to deeper soil layers in the apricot orchards. In the soil profiles, increasing Cl contents are not related to increasing δ2H and δ18O values. This finding suggests that the extreme deficit of soil water and dry layer developments is mainly caused by intense transpiration, rather than by evaporation alone. The occurrence and development of soil water deficit layers in the deep soil profiles were the dominant factors that caused tree growth degradation and gradual death, due to lack of adequate stored soil water in the deep layers for use during a long arid time. Thus, the large‐scale establishment of arbor trees will likely lead to long‐term soil desiccation in the arid or semiarid regions on the Loess Plateau.